A molecular survey of small ruminant hemotropic mycoplasmosis in Turkey, including first laboratory confirmed clinical cases caused by Mycoplasma ovis - Aktas, Munir; Ozubek, Sezayi (Elsevier, 2017)
Hemotropic mycoplasmas are emerging zoonotic pathogens that cause mild to severe hemolytic anemia. Blood samples and thin blood smears were collected from six sheep exhibiting clinical symptoms typical of hemolytic anemia. Coccoid and ring-shaped M. ovis were found on the surface of erythrocytes of infected sheep. Parasitemia ranged from 0.7% to 3.7% in individual smears. Clinical cases caused by Mycoplasma ovis were evaluated, and prevalence, based on DNA screening for the 16S rRNA gene of hemoplasmas in apparently healthy sheep (n = 328) and goats (n = 272) from the same area, was 11.3% (CI 8.1-15.2) and 6.2% (CI 3.7-9.8), respectively, a significant difference between species (p < 0.05). Sequences of the nearly complete 16S rRNA gene shared 99% identity with the corresponding published sequences for M. ovis and Mycoplasma wenyonii. The overall M. ovis prevalence in healthy animals was 9% (CI 6.8-11.6) with no significant differences in infection rate between young and adults (p > 0.05). The proportion of hemoplasma-positive small ruminants was higher with tick infestation (p < 0.05). The presence of tick-borne Babesia spp. and Theileria spp. was also significantly associated with ovine hemoplasma infection (p < 0.05) in the healthy sample. This is the first report of M. wenyonii in sheep. M. ovis should be considered in differential diagnosis in cases of high fever and anorexia in pastured sheep and goats.
Keywords: Ovine hemotropic mycoplasma; Mycoplasma ovis; Mycoplasma wenyonii; Sheep; Goats